Faktor-Faktor Yang Mempengaruhi Status Gizi Pada Remaja Gizi Lebih: Faktor-Faktor Yang Mempengaruhi Status Gizi Pada Remaja Overweight dan Obese - Kamaruddin, Iriyani; Kustiyah, Lilik; Riyadi, Hadi; Junus, Ruqayah (Amerta Nutrition, 2023)
Background: One of the target groups at risk of becoming overweight and obese is teenagers. East Kalimantan is one of the largest provinces in Indonesia with a prevalence of overweight and obesity in children aged 13-15 years with a body massa indeks for age ( BMI/A)  indicator of 19.1% in 2018, where overweight was 12.0% and obesity was 7.1%. Objectives: To analyze the factors that influence nutritional status in overweight and obese adolescents aged 11-15 years. Methods: This study is a cross-sectional survey conducted at State Junior High Schools in Samarinda City from January to March 2021. The sample size was 290 students, determined using the Lemeshow and David formula, and selected through simple random sampling. Data collection includes the characteristics of the subject and their parents, measurement of body weight and height, food consumption, nutritional behavior, physical activity, and exercise habits using interviews using questionnaires. Data were analyzed using the Kruskal-Wallis test and Logistic Regression test. Results: There are differences in the nutritional status of boys and girls (p=0.006), mother's education and occupation (p=0.007; p=0.007), father's and mother's nutritional status (p=0.001; p=0.014), exercise habits (p=0.009), protein adequacy level (p=0.000), and fat adequacy level (p=0.016). Conclusions: Gender, occupation, education, nutritional status, eating habits, exercise habits, level of protein adequacy, and level of fat adequacy influence the occurrence of overweight and obesity in adolescents. It is necessary to increase sports activities which must be done at least 3-5 times a week for 30 minutes intensively and get used to consuming 3-4 portions of vegetables and fruit daily, as well as paying attention to appropriate meal portions.